NURSES’ EXPERIENCES ON NURSING INTERVENTIONS FOR PATIENTS UNDERGOING HEMODIALYSIS AT INTENSIVE CARE UNIT, OF A PUBLIC HOSPITAL IN NAMIBIA - Jasmine Iimene; Simon Shalonda (Nurse and Holistic Care, 2026)
Background: Nurses play a fundamental role in specialized nursing units such as nephrology and Intensive Care Units (ICU) where patients undergo life- sustaining treatment such as Hemodialysis. Hemodialysis is performed in (ICU) regularly for critically ill patients with metabolic derangements to conserve life and alleviate suffering. Purpose: The aim of the study was to explore the experience of nurses on nursing intervention for patients undergoing hemodialysis treatment at ICU. Methods: A qualitative exploratory approach was used to explore nurses’ experiences regarding nursing interventions of patients undergoing hemodialysis. The target population includes all nurses with more than one year of working experience in ICU. Purposive sampling was used to select participants. Considering data saturation, seven participants were interviewed face to face using a structured interview guide. A tape-recorder was used to record participant’s interviews. Data was analyzed thematically. Results: Three themes and 7 sub-themes emerged from the study. The main themes emerged from the study are (i) The dynamic role of nurses in hemodialysis treatment, (ii) Patient assessment, preparation and readiness for hemodialysis, (iii) Managing patient’s co-morbidities before hemodialysis. Conclusion: Nurses are the first contact in any patient care including dialysis unit. They are expected to oversee the dialysis machine and continuous monitoring of patient’s condition for possible side effects. The study underscores the critical importance of nursing interventions in enhancing the quality of care for hemodialysis patients.